Standards for legitimate prosecution (Academic Journal of Internal Affairs, 2017)
By reviewing the case law, the author outlines possible developments in the field of prosecution with regard to the current and the proposed codification of the new Hungarian Criminal Procedure Code.
Keywords: prosecution; Criminal Procedure Code; case law